PHYSIQUE, BODY COMPOSITION AND AEROBIC PERFORMANCE OF MALE TEACHER EDUCATION STUDENTS - SZAKÁLY, Zsolt; LISZKAI, Zsuzsanna; LENGVÁRI, Balázs; JANKOV, István; BOGNÁR, József; FÜGEDI, Balázs (Studia Universitatis Babeş-Bolyai Educatio Artis Gymnasticae, 2016)
Students in teacher education programs will have all sorts of assignments related to education at the public school setting, so it is important for them to carry a healthy active way of life and become a role model in this area as well. The aim of our survey was to characterize the status of physique, body composition and aerobic performance of male teacher education students at the beginning of their first year in program and at the end. All first year male students were selected at the teacher training program at Apáczai Csere János Faculty, University of West Hungary (N=102). Results in most areas were within a normal adult range. There were no difference in the physique characteristics between students in general teaching program and students in PE and sport program (Height, Weight, Metric and Plastic Index), but there were significant difference in body composition and Cooper-test results. The results did not change significantly over the year. It would be important to support teacher education students with scheduled and professional health-related training program based upon their individual needs and expectations towards healthy active living.